Role of genetic variants in phase-II drug metabolizing genes as predictors of Drug-Induced Liver Injury (DILI) in patients on Anti-Tubercular drugs - Tavkar, Vrunda (Thapar Institute of Engineering and Technology, 2025)
Background: According to the World Health Organisation (WHO), Tuberculosis is the world's leading infectious killer and is still a major health threat around the world. Mycobacterium tuberculosis causes tuberculosis (TB), which mostly affects the lungs. It is treated with a mix of anti-tubercular drugs like isoniazid, rifampicin, ethambutol, and pyrazinamide. A significant number of TB patients get liver damage from the anti-TB drugs, which is called Anti-Tuberculosis Drug-Induced Liver Injury (AT-DILI). One of the major cause of hepatotoxicity is incomplete breakdown of the anti-TB drugs drug and build up of toxic intermediates in the liver. N-acetyltransferase 2 (NAT2) and UDPglucuronosyltransferase 2B7 (UGT2B7) are two examples of phase-II drug-metabolizing enzymes in the liver. Genetic variations in the genes that code for these enzymes can make them less effective and raise the risk of liver damage. Purpose: The goal of this study is to look into how certain genetic variants NAT2*5, NAT2*6, NAT2*7, and UGT2B7 influence susceptibility to get AT-DILI in North Indian population, who are on standard anti-TB treatment. Experimental Design: The study used a case-control design, with TB patients who developed AT-DILI (cases) and those who did not (controls), all of whom were getting standard anti-TB treatment. We took out genomic DNA and used PCR-RFLP methods to genotype certain SNPs in the NAT2 and UGT2B7 genes. We checked liver function (SGOT, SGPT, bilirubin) at the start and again during follow-ups and compared them to genotypes. A meta-analysis of 48 studies from around the world with more than 10,000 subjects was also done to look at the overall link between NAT2 polymorphisms and AT-DILI risk in different ethnic groups. The results showed that NAT2*5C was strongly linked to a higher risk of ATDILI under the recessive model and that there were variations in liver enzyme levels linked to enzyme phenotype. The meta-analysis supported these results, showing that slow acetylator genotypes have a threefold higher risk, especially in Asian and African populations. These results show that pharmacogenetic screening could help doctors choose safer and more effective TB treatments.
Keywords: Tuberculosis; Anti-Tubercular Drug-Induced Live Injury; NAT2 Polymorphism; UGT2B7 Polymorphsim; Meta Analysis